Adubação nitrogenada no feijoeiro após palhada de milho e braquiária no plantio direto - Carmeis Filho, Antonio Carlos De Almeida [UNESP]; da Cunha, Tatiana Pagan Loeiro [UNESP]; Mingotte, Fábio Luiz Checchio [UNESP]; do Amaral, Camila Baptista [UNESP]; Lemos, Leandro Borges [UNESP]; Filho, Domingos Fornasieri [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2014)
The present study was carried out to evaluate the agronomic and technological performance of common-bean crop following three straw mulch production system (sole corn, corn-Urochloa ruziziensis intercrop and sole U. ruziziensis) and topdressing nitrogen fertilization (0, 40, 80, 120 and 160 kg ha-1 of N) in the fourth year after the no-tillage system implementation. A randomized block design, in a splitplot array, with three replications was used. The use of U. ruziziensis intercropped with maize allowed a greater straw mulch formation and a more adequate coverage of the soil surface aiming the beans cultivation in succession. The nitrogen fertilization influenced the common-bean productivity in succession to U. ruziziensis unique and maize intercropped with U. ruziziensis. The common-bean crop in succession to the straw mulch production system with U. ruziziensis allowed higher grain production and sieve yield. The grain cooking time decreased due to the rates of N used in the dry bean crop in succession of maize exclusive.
Nitrogen fertilization on common bean in succession to maize and brachiaria in no-tillage
Keywords: Crop system; Phaseolus vulgaris L.; Topdressing nitrogen fertilization; Urochloa ruziziensis; Zea mays L.